Effect of temperature, flowering time and inflorescence length on yield and productivity of litchi (Litchi chinensis) cv. ‘Shahi’ - LAL, N; SINGH, A; KUMAR, A; MARBOH, E S; JAYSWAL, D K; PANDEY, S D; NATH, V (The Indian Journal of Agricultural Sciences, 2022)
The present study was carried out in 2017–18 at ICAR-NRC on Litchi, Muzaffarpur to assess the effect of temperature, flowering time and inflorescence length on yield of litchi (Litchi chinensis Sonn.) cv. Shahi. The study revealed that the temperature, flowering stage as well as length of inflorescence were positively correlated with florescence width (0.98) while fruit set was negatively correlated with temperature (-0.863). There was a strong correlation between fruit set and size of the inflorescence. Early-season flowering had higher fruit set (8.56%) as compared to mid (7.58%) and late-season (4.05%) flowering. Fruit set was critically reduced by 50% in late floweringplants resulting in drastic reduction in the total fruit yield. A strong positive correlation (0.84) was found between inflorescence hickness and fruit weight. Fruit and pulp weight were influenced by stage of flowering, as early flowering exhibited highest fruit weight (24.56 g) compared to mid and late flowering in which fruit weight was reduced by 35.42% and 50%, respectively.